EFEKTIFITAS RENDAMAN DAUN ANDONG (Cordyline fruticosa (L) A. Chev) SEBAGAI PENGGANTI EOSIN 2% PADA PEMERIKSAAN TELUR CACING SOIL TRANSMITTED HELMINTHS (STH) - Rizka Ayu Wahyuni; Ainun Rizqina; Nurbidayah Nurbidayah; Putri Kartika Sari (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Worm infection is still a health problem in developing countries like Indonesia. The prevalence of worms in Indonesia is generally still very high, especially among the less fortunate, with poor sanitation. Diagnosis of worm infection can be made by examining preparations using 2% Eosin dye. The simplest technique for examining intestinal nematode worm eggs is the native method, this technique uses 2% eosin reagent with the following objectives: to assess the various elements in preparations or preparations. Eosin itself is not easily decomposed and creates toxic and flammable waste, so a natural dye is needed for soaking horseradish leaves (Cordyline fruticosa (L) A. Chev) as an alternative dye. ) in coloring STH worm eggs. The research design used in this study was experimental. Andong leaves were soaked using 2N HCl for 24 hours. of 20%, 40%, 60%, 80% and 100% which gives effective results only at concentrations of 80% and 100%. Keyword : Soil Transmitted Helmint (STH), Eosin, Andong leaf